John Hughes yearbook collection [videorecording (DVD)] : the Breakfast club, Sixteen candles, Weird science - Hughes, John, 1950-2009; Ringwald, Molly; Hall, Anthony Michael; Nelson, Judd; Estevez, Emilio, 1962-; Sheedy, Ally; Gleason, Paul, 1939-2006; Dooley, Paul, 1928-; Henry, Justin; Mitchell-Smith, Ilan, 1969-; LeBrock, Kelly, 1960- (Universal Studios Home Entertainment, 2015)
Breakfast club: A diverse group of high school students--a jock, a metalhead, a weirdo, a princess, and a nerd - sharing a Saturday in detention at their high school for one minor infraction or another. Over the course of a day, they talk through the social barriers that ordinarily keep them apart, and new alliances are born, though not without a lot of pain first.